Offshore: Economic Deterrent or Necessity - I. B. Turuev (Vestnik MGIMO-Universiteta)
The downside of investment's addition rate in Russia, lack of capital investments result from "poor investment attractiveness". As a result, the companies' financial imbalance together with high investments risks lead to capital outflow from the country by virtue of offshores. Along with negative aspects connected with "financial oases" many advantages are given to the business community: lessening of tax payments, monetary privacy and confidentiality of operations. Taking in consideration the above and also the existence of specific international agreements concerning the avoidance of double taxation and offshore zones, the banner of the latter appears to be quite difficult and would divest the global economy of an important segment of global economic growth. The author performed a SWOT analysis of the role and the importance of offshores in international economy. Tolerant coexistence of local and global economic interests seems to be achievable by implementing a distinct circumspect and complex plan of measures aimed at the raise of the investment attractiveness of a country, for which the creation of "Skolkovo" and new Institutes for market development would not be sufficient. Transparent and oriented on business stability and safety provision of monitor and regulatory system, data interflow, improvement of prudential control on financial markets operations - are parts of measures that have to be accomplished in order to solve and exclude the problems associated with offshores. But the author also appeals to not forgetting that besides the offshores exists a number of such issues directly related to the outflow of capital as lowering of inflationary pace, enlargement of direct investment flow-in, support of social peace, which have to be handled for the purposes of improvement of domestic investment climate of countries with developing economy.